2008
DOI: 10.1088/0953-8984/20/31/315003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the luminescence properties of Er-, Nd- and Tm-doped Si–ZrO2CO-sputtered films

Abstract: Er-, Nd- and Tm-doped Si-yttria stabilized zirconia (YSZ) thin film samples were prepared by rf co-sputtering. Chemical composition of the samples was determined using energy-dispersive spectroscopy (EDS) and the structure of the films by x-ray diffraction (XRD). The samples were annealed to 700 °C. Photoluminescence (PL) measurements were performed for the visible and infrared. Excitation with 457.9 nm produces spectra in the visible range due mostly to defects in the YSZ matrix with a weak Si nanoparticle su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…It is worth to note that PLE spectrum, measured at 720 nm detection wavelength that corresponds to PL maximum of Si-NCs emission [17], was found to be similar to PLE spectrum presented by curve 6 in Fig.5. Similar PL properties were demonstrated for the Er-doped Si-rich-ZrO 2 films [23,24]. Similar PL properties were demonstrated for the Er-doped Si-rich-ZrO 2 films [23,24].…”
Section: Light Emission From the Filmssupporting
confidence: 75%
See 1 more Smart Citation
“…It is worth to note that PLE spectrum, measured at 720 nm detection wavelength that corresponds to PL maximum of Si-NCs emission [17], was found to be similar to PLE spectrum presented by curve 6 in Fig.5. Similar PL properties were demonstrated for the Er-doped Si-rich-ZrO 2 films [23,24]. Similar PL properties were demonstrated for the Er-doped Si-rich-ZrO 2 films [23,24].…”
Section: Light Emission From the Filmssupporting
confidence: 75%
“…Similar data were obtained in [22] and demonstrated that oxygen-related defects can take part in the excitation of Si nanoclusters in Si-rich-SiO 2 films. Meanwhile, it was shown that oxygen-deficient silicon centers (Si-ODCs) and oxygen interstitial defects are effective excitation paths for Er 3+ ions [23]. In this system, the achievement of Er emission under non-resonant excitation was ascribed to energy transfer from Si-ncs.…”
Section: Light Emission From the Filmsmentioning
confidence: 98%
“…The other bands were observed for the FX samples as reported in Refs. [21,36], with an additional band at 800 nm due to the SiQO surface states [37] related to the Si np present in these films. Both GX and FX samples present a weakening of hostrelated emissions as the Er 3+ emissions get stronger for excitation at 488.0 nm.…”
Section: Resultsmentioning
confidence: 97%
“…The Er ions must then be excited by efficient energy transfer from the numerous defects present in G6. It was already mentioned [21,36] that the Er ions in the FX samples are excited both by the defects and by the Si np present in these films. Nonradiative energy transfer from the ZrO 2 host to RE ions has been previously reported [34,53].…”
Section: Article In Pressmentioning
confidence: 90%
See 1 more Smart Citation